COMMUNITIES ARE NOT ALL CREATED EQUAL: DESIGNING ENVIRONMENTS TO PREVENT VIOLENCE. (7th October 2012) - Tsao, B; Davis, RA; Cohen, L
Abstract : Background: Violence and fear of violence are major factors that cause injury and disability, correspond to increased rates of chronic disease and health disparities, and fundamentally undermine health and well-being. Aims/Objectives/Purpose: Written for local government agencies and community practitioners, this paper presents evidence that violence is a health equity issue and describes prevention strategies, especially at the policy and systems levels, that promote the development of safe environments for everyone. Methods: Mixed methods were used, including a literature review on how the built environment and other community-level risk and resilience factors determine the likelihood of violence. It also incorporates practical lessons from seven years of working with U.S. cities to advance a public health approach to prevent youth violence before it occurs. Results/Outcome: Safety is not fairly distributed in society, and some U.S. communities and groups are far more exposed to the poor neighborhood conditions that give rise to violence. Violence disproportionately affects young people of color and those living in communities that have been subjected to high levels of disinvestment. Because community-level risk and resilience factors for violence are spread unequally, some neighborhoods experience disproportionately elevated rates of injury, disability, chronic diseases from prolonged stress, and other maladies. Significance/Contribution to the Field: This paper provides concrete evidence that preventing violence requires improving specific factors in community environments, such as in urban neighborhoods. The findings suggest that preventing violence is a critical strategy for sustainably reducing disparate outcomes in injury and premature death, and for achieving equity across diverse communities.